Histoire, mémoire et fiction dans le cinéma américain contemporain - Elie Yazbek (Conserveries Mémorielles)
The relation between cinema and history, between the past as we know it and its representation on the screen is a fascinating subject. However, inducing this topic without a reference to the viewer cannot be as complete as it should be because it neglects the problematical theme of the spectator’s memory, his situation facing a specific event and in front of the image of this event. This essential issue about the connection between history, its representation in films and the condition of the viewer involved into a scheme in which his “ memory flow”, emotions, and souvenirs are concerned, a scheme trying to replace the elapsed memories, is the subject if this essay.